Why is gold such a good catalyst for oxygen reduction in alkaline media? - Quaino, Paola Monica (2012)
The two faces of gold: The reduction of oxygen on gold electrodes in alkaline solutions has been investigated theoretically. The most favorable reaction leads directly to adsorbed O2- , but the activation energy for a two-step pathway, in which the first step is an outersphere electron transfer to give solvated O2-, is only slightly higher. d-band catalysis, which dominates oxygen reduction in acid media, plays no role. The reason why the reaction is slow in acid media is also explained.